PEDAGOGICAL METHODS OF CREATING INDEPENDENT EDUCATIONAL ASSIGNMENTS: DIDACTIC APPROACH - Khursanova, Laylo (MMIT Proceedings, 2023)
Globalization and information processes in the world, in independent educational tasks that arise in an innovative educational environment, require pedagogical-methodical changes, and in this regard, the importance of teaching in the module-credit system is increasing. In developed countries, “pedagogical education” is recognized as the main factor that ensures sustainable development, and international organizations and most of the countries of the world set an urgent task to improve the process and tools for assessing the quality of new education defined in the credit module system, and to put into practice the mechanisms that allow to determine the achieved results. The present paper discusses some issues related to the topic